2021
DOI: 10.1186/s12889-021-12126-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between first and second wave COVID-19 mortality in Italy

Abstract: Background The relation between the magnitude of successive waves of the COVID-19 outbreak within the same communities could be useful in predicting the scope of new outbreaks. Methods We investigated the extent to which COVID-19 mortality in Italy during the second wave was related to first wave mortality within the same provinces. We compared data on province-specific COVID-19 2020 mortality in two time periods, corresponding to the first wave (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In Italy, more than 16.6 million infections and over 164 thousand deaths were reported in two years [3]. The distribution was uneven across the country; especially in the first wave, the Northern regions were most affected [4]. The tight mobility restrictions (the lockdown) and the testing and tracing measures were essential for the decline of the spread of SARS-CoV-2 after the first wave, in June and July 2020 [5,6], due to the limited effective and specific therapies [7,8] and before the availability of an effective vaccination [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, more than 16.6 million infections and over 164 thousand deaths were reported in two years [3]. The distribution was uneven across the country; especially in the first wave, the Northern regions were most affected [4]. The tight mobility restrictions (the lockdown) and the testing and tracing measures were essential for the decline of the spread of SARS-CoV-2 after the first wave, in June and July 2020 [5,6], due to the limited effective and specific therapies [7,8] and before the availability of an effective vaccination [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, variations in hospitalized patients are estimated based on the trend of COVID-19’s spread. This period is used in many studies that examine the effects of covid-19 during the two years of the virus’s spread, including its mortality [ 45 ], the incidence on patients suffering from other diseases [ 46 ], and the quality of polluted cities [ 47 ]…”
Section: Methodsmentioning
confidence: 99%
“…During March 2020, the infected cases reached a high point and continued to May which is considered as the first wave of COVID-19 infection in Italy. Early studies have explained that during the first wave, the infection was spread disproportionately in all regions and related to a high morbidity and mortality (Vinceti et al 2021 ; Borghesi et al 2021 ).
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…Hence, the region was affected intensely like the first wave of the epidemic. Albeit the infection circulates throughout the regions more proportionately and several studies have shown that younger people were enormously infected in that time, the mortality rate dropped marginally than the first wave (Vinceti et al 2021 ; Bongiovanni et al 2021 ).…”
Section: Main Textmentioning
confidence: 99%